2003
DOI: 10.1207/s1532706xid030202
|View full text |Cite
|
Sign up to set email alerts
|

Identity Processes in Poor Adolescents: Exploring the Linkages Between Economic Disadvantage and the Primary Task of Adolescence

Abstract: Despite an abundance of literature on the topic of adolescent identity formation, little is known about the relationship between socioeconomic status and identity processes, particularly potential effects of poverty on identity formation. Three correlates of poverty-derogatory self-relevant information (in the form of social stigma, marginalization, and disparate treatment), limitations in opportunity structure, and excessive stress-are hypothesized to circumscribe identity processes in poor adolescents. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 25 publications
2
52
1
Order By: Relevance
“…In the absence of empirical research identifying specifi c barriers to personal identity development, we draw on relevant theoretical literature and highlight four specifi c types of barriers that are discussed here: (a) socioeconomic disadvantage [Phillips & Pittman, 2003], (b) differences in cultural orientation between immigrant people and the receiving society [Côté, 1993], (c) lack of social-institutional support for identity development [Côté, 2000], and (d) ethnicity-related barriers [Schwartz, 2005]. These four barrier types all involve limiting or constriction of the array of potential personal identity options and commitments available to the person.…”
Section: Personal Identity: Immigration-and Acculturation-related Barmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of empirical research identifying specifi c barriers to personal identity development, we draw on relevant theoretical literature and highlight four specifi c types of barriers that are discussed here: (a) socioeconomic disadvantage [Phillips & Pittman, 2003], (b) differences in cultural orientation between immigrant people and the receiving society [Côté, 1993], (c) lack of social-institutional support for identity development [Côté, 2000], and (d) ethnicity-related barriers [Schwartz, 2005]. These four barrier types all involve limiting or constriction of the array of potential personal identity options and commitments available to the person.…”
Section: Personal Identity: Immigration-and Acculturation-related Barmentioning
confidence: 99%
“…Moreover, immigrant people of color and those less acculturated to the receiving society may be more likely to be segregated from members of the receiving society [Musterd & Deurloo, 2002]. With respect to identity development, marginalization and socioeconomic disadvantage may be associated with a decrease in the number of prospective personal identity options available to young people [Phillips & Pittman, 2003;Yoder, 2000]. When the array of available personal identity alternatives is constrained, the likelihood is increased that an individual may not have access to a set of identity elements that he or she would like to select.…”
Section: Personal Identity: Immigration-and Acculturation-related Barmentioning
confidence: 99%
“…Problems associated with feeling accepted in church may also be exacerbated by the presence of children. Children are especially likely to feel alienated in church due particular, there is a strong sense of marginalization associated with being poor (Phillips and Pittman 2003). The lack of religious participation by low-income, white Catholics with children means that opportunities for both low-income adults and their children to develop vital civic skills and interact with people outside of their often-limited social networks are consequently severely restricted.…”
Section: Non-urban Urbanmentioning
confidence: 99%
“…In addition to factors such as age, gender, immigration policies, and years of living in the receiving society, BII is also predicted by factors such as personality traits, socioeconomic disadvantages (Phillips & Pittman, 2003 ), differences in cultural orientation between majority and minority groups (Côté, 1993 ), degree of similarity between the two cultures (Rudmin, 2003 ), lack of social and institutional support (Côté, 2000 ), and support for the maintenance of the heritage culture in the new society (Portes & Rumbaut, 2001 ). Moreover, it has been suggested that low bicultural identity integration is caused by the perception of being culturally isolated (Berry, 1990 ), diffi culties in intercultural relations (Tzeng & Jackson, 1994 ), and cultural and ethnic stereotypes and prejudices (Crocker & Major, 1989 ); all variables that are also linked with confl icting intergroup relations.…”
Section: Social Identifi Cation During Acculturationmentioning
confidence: 99%